High sensitive photometric assay of pancreatic lipase and clinical investigation of urinary lipase in patients with various histopathological types of primary glomerulonephritis - SOEZIMA, AKINORI; YOMOGIDA, SIGERU; SUZUKI, MITIHIKO; TUZI, MASATO; NAKABAYASI, KIMIMASA; KITAMOTO, KIYOSI; NAGASAWA, TOSHIHIKO (Nihon Jinzo Gakkai shi, 1990)
We measured the activity of urinary lipase by high sensitive photometric method using 1, 2-dirinoleoilglycerol as a substrate. Also, we investigated the clinical significance of the activity of urinary lipase in patients with chronic glomerulonephritis (GN) with special reference to the relation between the levels of the enzyme and histopathological changes of the kidney. Urinary activity of N-acetyl-β-D-glucosaminidase (NAG) and urinary β2-microglobulin (BMG) were also measured to compare the difference of renal handling of these 3 substances. We could obtain the following results; 1) Good coefficient of correlation was observed between the activity of urinary lipase and the excretion of urinary BMG. 2) No correla-tion was observed between the activity of urinary lipase and the amount of urinary NAG in patients with chronic GN. 3) In some of the cases with secondary tubulointerstitial edema and inflammatory infiltration, the values of the activity of urinary lipase were markedly elevated. These results suggested that lipase was removed from the serum mainly by glomerular filtration and reabsorbed almost completely by tubular epithelial cells like the renal handling of BMG. In contrast, NAG secreted through the different renal metabolism in proximal tubule. The activity of urinary lipase might be a diagnostic marker for the secondary acute tubulointerstitial lesions in patients with chronic GN.